Austerity : the lived experience - Evans, Bryan M., 1960-; McBride, Stephen, 1947- (University of Toronto Press, 2017)
Bryan M. Evans, Stephen McBride, and their contributors delve further into the more practical, ground-level side of the austerity equation in Austerity: The Lived Experience.